Pathological Diagnostic Testing and Biomarkers for Perioperative System Therapy Pathologische Diagnostik und Biomarker für die perioperative Systemtherapie - Erber, Ramona (Zentralblatt für Chirurgie, 2024)
Optimal personalized treatment planning for resectable lung cancer requires quality-assured, standardized and prompt processing of tissue samples in pathological laboratories, as well as the determination of relevant predictive and prognostic biomarkers. Pathological diagnostic testing includes histological tumor typing, staging and tumor grading, resection status and, if necessary, regression grading after neoadjuvant systemic therapy. Histopathological typing is performed according to the current WHO classification and includes adenocarcinomas, squamous cell carcinomas, other non-small cell lung carcinomas (NSCLCs), carcinoids, small cell and large cell neuroendocrine carcinomas. Standardized tumor grading currently plays an important role in invasive non-mucinous adenocarcinoma in particular and enables prognostic risk assessment. The R classification and regression grading are also prognostically relevant. In the early stages of NSCLC, molecular biomarkers such as EGFR, ALK and PD-L1, are relevant for decisions on individual treatment. Testing is performed on FFPE tissue samples and must be carried out in a quality-assured manner and in accordance with international standards.
CRIS-Team Scopus Importer:2024-08-23
Keywords: immune checkpoint inhibitor; lung cancer; NSCLC; pathology; predictive biomarker